Fly away portable fly repellent / Norfarhana Balqis Husin - Husin, Norfarhana (2020)
This business is based on sole proprietorship. Farhana Repel Sdn Bhd is the shop that will focuses on the repeller product industry in Malaysia. This shop will be selling animal repellent. However, the main products that are a focus and will be selling in Farhana Repel shop are Fly Away products (Portable Fly Repellent) which have the unique functions and characteristics repellent than other repeller. The Fly Away is different from other repeller that were sold at other shops. This is because the product that we sell in this shop is different from others and only focusing on selling the repellent products.Farhana Repel Shop is one of the shops that will operate in Taman Indahpura Kulai Johor.This place is a strategy place. This is because it is near the people's regencies. Therefore, we can attract all kinds of age of people to enter the shop. This is because the Fly Away repellent product that will be sold is suitable for all people to use it.